Perancangan Aplikasi Android Sistem Informasi Masjid Taklim Kecamatan Purwosari - Ahmad Suliantoro (The Indonesian Journal of Computer Science Research, 2022)
Agencies need information systems to contain various data that includes everything inside and outside the agency. The taklim mosque information system is an integrated system with mosque data information. Information contains taklim mosque data. This research will focus on general data and waqf data. General data contains main data regarding mosque information, while waqf data contains information on land data that has been waqf. The application design uses the RAD (Rapid Development Application) method. Application development using mit app inventor. Data storage using Google Drive connected to Google Forms. Application testing uses black box testing techniques. In this study produces an android-based data input application.